Genetic Diversity Analysis of cpDNA in Turkish Abies Taxa - CELIK ALTUNOGLU, Yasemin; GÜNEY, Kerim; BALOGLU, Pınar; BALOGLU, Mehmet (Kastamonu University, 2021)
Aim of study: Five Abies taxa naturally distributed in Turkey. Abies nordmanniana has three subspecies and A. cilica has two subspecies. In this study, we aimed to show phylogenetic relationships both in Turkish taxa and in other Abies taxa from around the world based on cpDNA regions, trnR-trnN and rps18-rpl20 regions. Material and methods: Following CTAB-based DNA isolation method, the relevant fir DNA regions were amplified and sequenced. Phylogenetic trees were constructed using maximum likelihood method with 1000 bootstrap replicates. Main results: It was difficult to make distinctions among the Turkish Abies taxa based on the sequenced DNA regions. Based on rps18-rpl20 phylogenetic tree, some members of Abies cilicica subsp. isaurica, A. nordmanniana subsp. equi-trojani and A. cilicica subsp. cilicica were in the same clade with A. spectabilis and A. densa; However, some members of A. nordmanniana subsp. bornmuelleriana, A. cilicica subsp. isaurica and A. nordmanniana subsp. equi-trojani were placed in a clade with A. alba placed near Turkey and A. amabilis known from North America. Highlights: This study provides new insights into the distribution of cpDNA variation in Abies species in Turkey and the genetic variation between firs in Turkey and the rest of the world.
Keywords: Göknar; Moleküler Taksonomi; Kloroplast DNA Bölgesi; Fir; Molecular Taxonomy; Chloroplast DNA Region